Wakaf Uang Sebagai Instrumen Perkembangan Ekonomi Islam - Chusma, Nafisah Maulidia Chusma; Sa’diyah, Halimatus; Latifah, Fitri Nur (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2022)
This study aims to determine the value of cash waqf as an instrument of Islamic economic development. Cash waqf according to the report of the Indonesian Waqf Agency has a very significant potential every year. This is one of the opportunities, the spread of money investment in productive sectors such as the halal business sectors, the real sector, to the halal sector which currently has very crucial prospects. The research uses secondary data in describing the discussion, so the approach used is a normative juridical approach. Thus the author uses a descriptive qualitative method in this article. The results of the study indicate that cash waqf funds currently tend to be channeled to the halal investment sector, where the proceeds from these investments are channeled to small businesses, and the world of education. In this case, cash waqf also indirectly involves financial institutions such as Islamic banking as nadzir which plays an important role in distributing cash waqf funds. It can be seen that cash waqf is able to play a role in developing the Islamic economy. Keyword: Waqf, Money Waqf, Islamic Economic.